2006
DOI: 10.1590/s1517-86922006000600019
|View full text |Cite
|
Sign up to set email alerts
|

Fatores intrínsecos do custo energético da locomoção durante a natação

Abstract: The amount of metabolic energy spent in transporting the body mass of the subject over a unit of distance has been defined as the energy cost of locomotion, or regarding to swimming, cost of swimming. The differences in the cost of swimming between the individuals seem to be influenced by two main factors, the hydrodynamic resistance and technical skill of the swimmer. The lower cost of swimming showed by females has been attributed to a smaller hydrodynamic resistance due to their smaller size, larger percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
1
8
0
3
Order By: Relevance
“…Fish metabolism is also affected by many ecological factors [39,40]. Stimulation caused by changing hydraulic factors in fish courses will often lead to fish exhibiting behavioral responses, and these behavioral changes can cause significant metabolic changes, which in turn cause changes in energy requirements [41].…”
Section: Discussionmentioning
confidence: 99%
“…Fish metabolism is also affected by many ecological factors [39,40]. Stimulation caused by changing hydraulic factors in fish courses will often lead to fish exhibiting behavioral responses, and these behavioral changes can cause significant metabolic changes, which in turn cause changes in energy requirements [41].…”
Section: Discussionmentioning
confidence: 99%
“…Our results, corroborates the idea of evaluating peak height velocity (PHV) as a biological maturation indicator 25 and a predictor related to generating propulsive force of the arm in young swimmers. In addition, Caputo et al 26 reported that for short duration events in which the power production capacity is considered a key variable, physical characteristics such as body height, arm span, body composition, and somatotype can also contribute to the level of performance. These morphological attributes largely depend on genetic factors and may have a decisive influence on swimming performance 27 .…”
Section: Discussionmentioning
confidence: 99%
“…Moving through the aquatic environment requires greater energy expenditure [32], given that water is approximately 800 times denser than air, and therefore, the swimmer will have to overcome the resistance it offers in order to move forward [33]. Furthermore, only part of the force applied by the swimmer is translated into propulsive force [34], which is what allows the swimmer to move forward. Therefore, another important factor that determines success in this sport is related to the athlete's ability to maximise propulsive force and reduce resistance to progress offered by the aquatic environment [35], which in turn is closely related to, among other aspects, the technical ability of the individual.…”
Section: Of 19mentioning
confidence: 99%